Antimicrobial Efficacy of Garcinia Cambogia Fruit Extract Against Food Borne Bacterial Pathogens, In vitro and in Chicken Meat : doi: 10.5958/2581-6616.2020.00001.8 - Bhuvana, K. S.; Mandal, P. K.; Pal, U. K.; Antony, P. X.; Kasthuri , S. (Journal of Meat Science, 2021)
The use of natural preservatives to increase the shelf-life of meat and meat products is a promising trend. The present study was done to evaluate the efficacy of the crude extract of Garcinia cambogia fruit as natural preservative in chicken meat. The in vitro antimicrobial efficacy of a crude extract of G. cambogia fruit against common food-borne bacterial pathogens was evaluated by agar diffusion assay. Minced chicken was inoculated with Escherichia coli and Salmonella Typhimurium and the effect of the extract on these pathogens was studied during storage under refrigeration. The extract was tested to evaluate its efficacy as a decontaminating agent in the form of a dip solution. The extract of G. cambogia fruit was found to have a high in vitro antimicrobial activity against the bacterial pathogens such as Bacillus cereus, Staphylococcus aureus, Salmonella Typhimurium, Escherichia coli, Klebsiella pneumoniae, Shigella flexneri, Pseudomonas aeruginosa and Escherichia coli O157:H7. Both 1 and 2% extract groups significantly (P<0.01) reduced the counts of Escherichia coli and Salmonella typhimurium inoculated into minced chicken meat under refrigeration storage but no significant (P>0.05) difference in antimicrobial activity was observed between levels. The evaluation of the extract as a decontaminating agent at levels of 0.5, 1 and 1.5% (v/v solution) revealed a significant (P<0.01) decrease in case of both SPC and coliform counts for selected cuts dipped in the solution of the extract. The results showed excellent antimicrobial efficacy of the crude extract of Garcinia cambogia fruit and found to be suitable decontam inating agent for chicken cuts.